Modeling techniques for photovoltaic systems under mismatching conditions (2018)
There is a growing interest in photovoltaic (PV) systems since they represent a strong option for power supply around the world. Therefore, there is also a growing necessity for developing tools to analyze the behavior of the PV systems under realistic conditions. Hence, better planning, design and operative strategies can be developed. This thesis addresses the issues related with the modeling of PV systems operating under uniform and mismatched irradiance conditions. Moreover, this work considers the PV array connected in different configurations. In this way, the first part of the thesis presents the state-of-the-art in modeling techniques, it including circuital representations of PV cells and modules and its behavior under different scenarios, operation characteristics of different configurations, the effects of the operation under shading conditions, available modeling techniques, among others. The Series-Parallel (SP) is one of the most studied configuration, then some modeling techniques for SP arrays are introduced in this thesis. Such procedures allowed to understand the operation of PV arrays to detect the main aspects that need to be considered in a modeling process. The first technique is based on the ideal single diode model but considers the operation of the modules in the second quadrant by using a linear model to represent the bypass diodes. The approach allows to avoid introducing errors which may cause overestimation in the predicted power when the array is exposed to partial shading conditions. A second approach introduces a combination between the single diode model to represent the modules and a linear model to represent the bypass diodes; the mathematical relationships between the voltages and currents in the modules are typically implicit expression which requires the use of special functions as the Lambert-W function. However, the approach introduced a procedure to avoid the use of such a function, which allows to reduce the computation bur- den. The third approach is based on the single diode model for representing the PV modules and the Schottky model for representing the bypass diode; it proposes a procedure to calculate the maximum power point (MPP) for a given condition operation, without the need of calculating the whole power vs. voltage curve as it is typically performed. Instead, the procedure calculates some points in the neighborhood of the local maximum power points (LMPP) to define the MPP, it providing a fast calculation of the power delivered by the array for a given operating condition. Moreover, the procedure applies the mathematical treatment introduced in the second approach to avoid using the Lambert-W function. Finally, the fourth approach is based on simplified versions of the single diode model and the Schottky model; such versions are named ideal single diode model and ideal switch model, respectively. The main purpose of the approach is to introduce a procedure for modeling the shading considering its dynamic behavior which enables to achieve a more realistic operating condition to calculate the power provided by the array. Other PV configurations, such as the Total Cross Tied (TCT) or the Bridge Linked (BL), may present better performances in comparison with the SP configuration for some opera- ting conditions. However, there is no detailed procedures for modeling such configurations. In fact, the available techniques allow to analyze only one configuration which means that for each configuration a modeling algorithm is required, it making the evaluation of several configuration a complex and time consuming task. In other words, there is not a modeling procedure capable to represent any configuration. Therefore, a general modeling procedure for analyzing any PV configuration operating under uniform or shading conditions is introduced in this thesis. The possibility of studying any connection allows to consider structures without any connection pattern, in this way the thesis introduces the concept of irregular structure as a new option for obtaining improved power profiles at a particular operating condition. The general modeling procedure is a useful tool for reconfigurations analysis, planning and design of PV arrays. All the modeling approaches presented in this work were validated through simulations and experimental tests. Most of them were implemented using Matlab scripts based on widely known programming structures and mathematical functions, those codes can be reproduced in languages such as C and C + +